1996
DOI: 10.1042/bj3200335
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of the thrombin receptor: identification of potential activators and inactivators

Abstract: The kinetic parameters were determined for the hydrolysis of a peptide based on the activation site of the thrombin receptor (residues 38-60) by thrombin and 12 other proteases. The kcat and Km values for the cleavage of this peptide (TR39-40) by thrombin were 107 s-1 and 1.3 microM; the kcat/Km of TR39-40 is among the highest observed for thrombin. A model is presented that reconciles the parameters for cleavage of the peptide with the concentration dependence of cellular responses to thrombin. Cleavage of TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 62 publications
5
58
1
1
Order By: Relevance
“…It has been reported that plasmin interacts with PAR-1 based on its activity toward a synthetic peptide designed to represent the thrombin cleavage site (25), albeit with an activity that is slower than thrombin by about 10-fold. Kuliopulos et al (26) showed with calcium mobilization studies that plasmin has a low affinity for the traditional thrombin cleavage site on PAR-1 and a higher affinity for a cleavage site that is further downstream; in effect, plasmin is more likely to make PAR-1 refractory to further thrombin stimulation than to stimulate calcium mobilization.…”
Section: Fig 2 Plasmin Desensitizes Par-1 or Par-4 After Long Incubmentioning
confidence: 99%
“…It has been reported that plasmin interacts with PAR-1 based on its activity toward a synthetic peptide designed to represent the thrombin cleavage site (25), albeit with an activity that is slower than thrombin by about 10-fold. Kuliopulos et al (26) showed with calcium mobilization studies that plasmin has a low affinity for the traditional thrombin cleavage site on PAR-1 and a higher affinity for a cleavage site that is further downstream; in effect, plasmin is more likely to make PAR-1 refractory to further thrombin stimulation than to stimulate calcium mobilization.…”
Section: Fig 2 Plasmin Desensitizes Par-1 or Par-4 After Long Incubmentioning
confidence: 99%
“…Plasmin can bind with high affinity to endothelial cells (Bauer et a!., 1984;Hall et aI., 1991), eliciting functional responses through a specific plasmin receptor, but by cleaving at Arg 41 _Ser 42 it also has the potential to acti vate PAR-I (Parry et a!., 1996). Plasmin is known to affect platelet activation; at high concentrations it in creases, but at lower concentrations it inhibits thrombin induced platelet activation (Kimura et aI., 1996;Kin lough-Rathbone et aI., 1997).…”
mentioning
confidence: 99%
“…GrA has been considered as a low-affinity ligand of PAR-1 (Parry et al 1996;Steinhoff et al 2005;Suidan et al 1994). For instance, this protease induced neurite retraction, which was inhibited in the presence of an anti-PAR-1 antibody (Suidan et al 1994).…”
Section: Introductionmentioning
confidence: 99%